Effects of zinc oxide and condensed tannins on the growth performance and intestinal health of weaned piglets in ETEC-challenged environment - Yi, Hongbo; Wang, Zhikang; Yang, Bijing; Yang, Xuefeng; Gao, Kaiguo; Xiong, Yunxia; Wu, Qiwen; Qiu, Yueqin; Hu, Shenglan; Wang, Li; Jiang, Zongyong (Frontiers in Microbiology, 2023)
This experiment was conducted to evaluate effects of zine oxide (ZnO) and condensed tannins (CT), independently or in combination, on the growth performance and intestinal health of weaned piglets in enterotoxigenic Escherichia coli (ETEC-K88) challenged environment. Randomly divided 72 weaned piglets into 4 groups. Dietary treatments included the following: basic diet group (CON), 1500 mg/kg zinc oxide group (ZnO), 1000 mg/kg condensed tannins group (CT), and 1500 mg/kg zinc oxide + 1000 mg/kg condensed tannins group (ZnO + CT). Dietary ZnO supplementation increased average daily gain (ADG) from 0 to14 d (P <0.05), and average daily feed intake (ADFI) from 15 to 28 d and from 0 to 28 d (P <0.01), decreased diarrhea rate from 0 to 14 d, 15 to 28 d and 0 to 28 d (P <0.01). The effect of CT on reducing diarrhea rate and diarrhea index was similar to the results of ZnO. Compared with the CON group, ZnO increased the ileum villus height and improved intestinal barrier function by increasing the content of mucin 2 (MUC-2) in ileum mucosa and the mRNA expression of zonula occludens-1 (ZO-1) in duodenum and jejunum (P <0.01). A significant interactive effect was observed in pigs supplemented with ZnO and CT in reducing the ileum villus height (P <0.05), while the content of MUC-2 in jejunum was increased (P <0.01). Moreover, the mRNA expression of cystic fibrosis transmembrane conductance regulator (CFTR) was reduced in ZnO group, while the aquaporin3 (AQP3) and aquaporin8 (AQP8) were increased (P <0.05). And the effects of CT on diarrhea-related channel genes was similar to that of ZnO. In addition, pigs receiving ZnO diet had higher abundance of phylum Bacteroidetes, and genera Prevotella, and lower phylum Firmicutes and genera Lactobacillus in colonic contents. In summary, ZnO improved growth performance and intestinal health of weaned pigs. Results indicated that ZnO and CT alleviated diarrhea, but CT couldn’t act as a substitute for ZnO in this study. This study provides a theoretical basis for the application of ZnO in weaning piglet production practices, we also explored whether CT could be used as an alternative to ZnO.